Female Physicians in Maternal–Fetal Medicine: A 32-Year Perspective - Blackstone, Jacquelyn; Will, Vanessa K.; Rayburn, William F. (American Journal of Perinatology, 2018)
Objective To examine trends of female physicians either pursuing fellowships or in active practice in maternal–fetal medicine (MFM).Methods This observational study examined complete sets of MFM fellows and active members of the Society for Maternal-Fetal Medicine (SMFM) between 1985 and 2016. Databases from SMFM, American College of Obstetricians and Gynecologists (ACOG), and Accreditation Council for Graduate Medical Education were used. Analysis of covariance testing was used to assess interactions over time between groups.Results The proportion of female MFM fellows increased steadily from 17.1% in 1985 to 72.5% in 2016. The proportion of females grew more rapidly among the MFM fellows than obstetrics and gynecology (ob-gyn) residents (2.1 vs. 1.4% per year; p = 0.001) and among those who were active SMFM members than ACOG Fellows (1.4 vs. 1.2% per year; p = 0.013). Slightly more than half (52.4%) of all SMFM members are now female and will approach two-thirds (64.4%) by 2025 (compared with 53.4% in 2016 and 65.3% in 2025 of ACOG fellows).Conclusion The rising proportion of female MFM fellows is directly related to the high number of female ob-gyn residents. Females comprise slightly more than half of all active SMFM members now and projected to approach two-thirds by 2025.
Keywords: fellowship; female; gender diversity; maternal–fetal medicine; residency